2020
DOI: 10.5296/jsel.v8i1.16434
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Direct and Indirect Written Corrective Feedback on English Collocation Competency: A Quasi – Experiment

Abstract: The primary aim of this study is to investigate the effectiveness of direct and indirect written corrective feedback (WCF) on English collocational competency of high-performing ESL learners. The study also sought to compare possible differences in the effect of two WCF strategies that help the researcher in identifying the appropriate WCF strategy in improving learners’ collocational competency in the context of the study. Additionally, retention effect of WCF is also investigated in delayed post-tests. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This has firmly supported the quantitative results in harmonious perspective which were in line with several studies (e.g. Ahmadi, Maftoon & Mehrdad, 2012;Ferris, 2006;Fhaeizdhyall, 2020;Hosseiny, 2014;Karim & Nassaji, 2018) which indicated that students deployed the explicit feedback more consistently and effectively than the implicit feedback. They could improve their language accuracy during the revision of passage composition.…”
Section: Difference Between An Implicit and An Explicit Feedbacksupporting
confidence: 90%
“…This has firmly supported the quantitative results in harmonious perspective which were in line with several studies (e.g. Ahmadi, Maftoon & Mehrdad, 2012;Ferris, 2006;Fhaeizdhyall, 2020;Hosseiny, 2014;Karim & Nassaji, 2018) which indicated that students deployed the explicit feedback more consistently and effectively than the implicit feedback. They could improve their language accuracy during the revision of passage composition.…”
Section: Difference Between An Implicit and An Explicit Feedbacksupporting
confidence: 90%